Preparation method of corrugated paper-based biodegradable mulching film

By dismantling and activating hydrogen bonds in corrugated paper fibers and adding long fibers to the slurry to form an interlaced spatial network framework, the problem of low reuse value of corrugated paper is solved, and high-performance cellulose-based agricultural mulch is prepared, achieving the goal of biodegradability and resource recycling.

CN119531168AActive Publication Date: 2025-02-28LIUPANSHUI NORMAL UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411709788.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Corrugated paper with low reuse value has poor mechanical properties and cannot be effectively reused due to problems such as shortening of fibers, co-crystallization of fibers, shrinking of fiber pore walls and hydrogen bonding between fibers, and ultimately becomes municipal solid waste.

Method used

Drawing on the hydrogen bond fracture mechanism of natural polymer cellulose, hydrogen bonds in fibers are dismantled and activated through chemical means, so that the fiber pores are reopened and the crystallinity is reduced. The alkali/urinary solution is used to partially dissolve the cellulose with low polymerization on the surface of corrugated paper fibers, and an appropriate amount of long fibers is added to the slurry. The spatial network skeleton with long and short fibers interlaced through the solution casting film process, and the cellulose solution is evenly filled in between. Finally, the plastic film is cured and shaped by solvent evaporation.

Benefits of technology

Cellulose-based agricultural mulch with a "reinforced concrete" structure was prepared, with significantly improved mechanical properties, meeting the needs of agricultural mulch, and having good biodegradability, reducing environmental pollution, promoting the recycling and sustainable development of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a preparation method of a corrugated paper-based biodegradable mulching film, which is an innovative method for preparing a cellulose-based biodegradable agricultural mulching film by taking waste paper with low recovery value, especially corrugated paper fibers for packaging, as raw materials through a solution casting film surface sizing process. The method effectively solves the problems of fiber pore wall shrinkage and cellulose co-crystallization caused by a repeated wetting-drying process. The prepared mulching film has excellent physical properties, heat preservation and soil moisture conservation effects and biodegradability, meets the use requirements of agricultural mulching films, solves the problem of white pollution caused by traditional plastic mulching films, and promotes cyclic utilization and sustainable development of resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a technology for preparing agricultural mulch films, and in particular to a method for preparing a corrugated paper-based biodegradable mulch film. Background Art

[0002] The development of biodegradable mulch is an effective way to solve the contradiction between the "white pollution" caused by the application of agricultural plastic mulch and the increase in crop yields and incomes. Cellulose-based mulch can automatically adjust the pressure difference between the inside and outside of the soil, oxygen content, temperature and humidity, improve the activity of soil microorganisms, increase the survival rate and growth rate of plants to increase crop yields, etc., and its raw materials are renewable, biodegradable, and environmentally non-toxic, which has attracted much attention.

[0003] Corrugated paper has become the largest and most commonly used packaging material in the logistics and express delivery industry due to its low cost, light weight, easy processing, high strength, excellent printing adaptability, and convenient storage and transportation. With the rapid rise of the logistics and express delivery industry, the application of corrugated paper has also ushered in rapid development. Corrugated paper is made of plant fibers using a series of processes such as wet papermaking. After use, it can be reused through a recycling system. However, due to repeated swelling-drying processes, the recycled fibers will undergo some irreversible changes such as fiber shortening, fiber co-crystallization, fiber pore wall shrinkage, and hydrogen bonds between fibers, which significantly reduce the swelling ability and softness of the fibers, resulting in low mechanical properties of the paper such as tensile strength, bursting resistance, and tear resistance, which makes it lose the value of recycled papermaking. In theory, recycled fibers can be recycled 6-7 times, but in fact, due to fiber keratinization, papermaking additives, fiber mixing, etc., the number of times they are reused is greatly reduced. The average number of times recycled in the EU is 3.5 times, and the average number of times recycled globally is 2.4 times. This means that the recycling of corrugated paper can only temporarily alleviate the problems of raw material shortage, high energy consumption and environmental pollution in the papermaking industry, and cannot change its property of eventually becoming municipal solid waste.

[0004] Therefore, it is urgent to develop a technical route that can realize the resource utilization of corrugated paper to promote its comprehensive recycling and sustainable development. Summary of the invention

[0005] In order to completely solve the chronic problems of low-recycling-value waste corrugated paper / boxes, such as fiber shortening, fiber co-crystallization, fiber pore wall shrinkage, hydrogen bonds between fibers, etc., which lead to poor mechanical properties of the finished paper and eventually become municipal solid waste, the present invention proposes to learn from the hydrogen bond breaking mechanism of natural polymer cellulose, use chemical means to disassemble and activate the hydrogen bonds in the fibers, so that the originally closed fiber pores are reopened and the crystallinity is reduced, and at the same time, alkali / urine solution is used to partially dissolve the low-polymerization degree cellulose on the surface of the corrugated paper fibers, and an appropriate amount of long fibers are added to the slurry to make up for the short fibers of the recycled corrugated paper. A solution casting process is used to form a spatial network skeleton in which long and short fibers are staggered and independently arranged, and the cellulose solution is evenly filled in between, and then the solvent evaporation method is used to solidify and shape the mulch, and finally glue is applied and dried to prepare a cellulose-based agricultural mulch with a "reinforced concrete" structure.

[0006] Based on the above problems, the present application provides a method for preparing a corrugated paper-based biodegradable mulch film, the method comprising the following steps:

[0007] S1. Soak the corrugated paper scraps in a sodium hydroxide solution with a concentration of 1%-3% at room temperature for 12-24 hours, and then perform ultrasonic treatment; during the ultrasonic process, the rubber and ink foam floating on the surface are manually scraped off with a scraper to obtain the degummed and inked slurry; the degummed and inked slurry is poured into a 200-300 mesh pulp bag for centrifugal separation to obtain degummed and deinked corrugated paper pulp fibers;

[0008] The solid-liquid ratio of corrugated paper scraps to sodium hydroxide solution is 1:15 (g:ml);

[0009] S2. The degummed and deinked corrugated pulp fibers in S1 are crushed to obtain pulp board fibers; the pulp board fibers are added to softened tap water at a solid-liquid ratio of 1:5-1:50 (g:ml), and the fibers are soaked at room temperature for 4-6 hours to perform fiber decomposition, and after decomposition, the fibers are transferred to a 200-300 mesh pulp bag for centrifugal separation to obtain decomposition long fiber wet pulp;

[0010] S3. Add the long fiber wet pulp of S2 to the alkaline urine solution at a solid-liquid ratio of 1:5-1:2500; then stir for 3-5 minutes at room temperature; after stirring, add the corrugated paper pulp fiber obtained from S1 at a solid-liquid ratio of 1.96%-1.6%; continue stirring for 1-2 minutes to obtain a viscous mixed pulp;

[0011] The stirring speed is 1000rpm-2000rpm;

[0012] S4. Pour the viscous mixed slurry obtained in S3 into a mold and shake it, then solidify it. After it is shaped, take it out and cool it to room temperature. Pour 100-300 ml of cellulose hydrogen bond reconstruction liquid into it, let it stand for 3-8 minutes, remove the hydrogen bond reconstruction liquid, and then treat the sample with softened tap water to make it neutral;

[0013] The curing temperature is 30-60°C and the curing time is 4-8h. The specific operation of the softened tap water treatment is to repeatedly add 100-300ml of softened tap water, soak for 3-5min and then dump it to obtain a wetland film.

[0014] S5: Spread the wet film in S4 between two filter cloths, and then place absorbent felt on both sides, remove a large amount of moisture from the wet film by using a roller wet method, and then apply a film performance improvement functional additive to both sides of the film and let it stand for 10-15 minutes, and then place the film in a vacuum flat plate dryer preheated to 60-95° C. and dry it for 5-10 minutes to obtain a corrugated paper-based biodegradable film;

[0015] The amount of the functional additive for improving the performance of the mulch film is 5-20 ml, 1:5-1:1000.

[0016] Furthermore, the ultrasonic power of the ultrasonic treatment of S1 is 40%-100%; the temperature is 40-80°C; the time is 5-60min; and the ultrasonic frequency is 40-140kHz.

[0017] Furthermore, the rotation speed of the fiber decomposition is 500-2000 rpm, and the time is 3-5 minutes.

[0018] Furthermore, the mass ratio of long and short fibers in S3 is controlled within the range of 8%-20%.

[0019] Furthermore, the alkaline urine solution in S3 is a 1%-10% sodium hydroxide / 20%-2% urea aqueous solution that has been precooled to -5 to -20°C.

[0020] Furthermore, the hydrogen bond reconstruction solution of S4 is one or a mixture of 7% ammonium sulfate solution, 5% sodium sulfate solution, and 5% sulfuric acid solution.

[0021] Furthermore, the method for removing moisture from S5 is as follows: the wetland membrane is laid flat between two filter cloths, absorbent felt is placed on both sides, and a large amount of moisture from the wetland membrane is removed by a roller wet method.

[0022] Furthermore, the oscillation mode in S4 is up-and-down seesaw oscillation, or horizontal rotary oscillation, or horizontal reciprocating oscillation, or a combination of several oscillation modes, with an oscillation time of 3-10 minutes and a rotation speed of 40-400 rpm.

[0023] Furthermore, the functional additive for improving the performance of the ground film of S5 can be one or a mixture of cationic dispersed rosin glue, polyamide epichlorohydrin resin, fly ash, cationic polyacrylamide, cationic starch, carboxymethyl cellulose, alkyl ketene dimer, paraffin emulsion, bisstearamide, phosphate starch, polyethylene oxide, gelatin, polyvinyl alcohol, and glycerol.

[0024] Furthermore, the method further comprises the following steps:

[0025] S6 measures the quantity, thickness, tensile strength, tear strength, bursting strength, folding strength, water vapor barrier properties, and composting degradation properties of the corrugated paper-based biodegradable mulch film obtained in S5;

[0026] S7 tests the heat preservation and moisture conservation effects, surface laying and soil burial degradation degree, and crop planting effects of the corrugated paper-based biodegradable mulch obtained by S5.

[0027] Beneficial Effects

[0028] (1) Environmental protection and sustainability: The present invention uses low-recyclable corrugated paper as raw material and successfully prepares biodegradable agricultural mulch through a series of chemical and physical treatments, which completely solves the chronic problem that low-recyclable corrugated paper eventually becomes municipal solid waste. The low-recyclable corrugated paper is effectively utilized as a resource, which not only reduces environmental pollution but also promotes the recycling and sustainable development of resources.

[0029] (2) Innovative technology and process: The present invention draws on the hydrogen bond breaking mechanism of natural polymer cellulose, uses chemical means to disassemble and reactivate the hydrogen bonds in the fiber, and solves the problems of fiber pore wall shrinkage and cellulose co-crystallization caused by repeated wetting-drying process; uses low-temperature alkali / urine solution to partially dissolve the low-polymerization cellulose on the surface of corrugated paper fiber, and then adds an appropriate amount of long fiber, and uses oscillation to make its structure a microscopic morphology in which long and short fibers are disorderly self-assembled and an appropriate amount of cellulose film is uniformly interspersed between its network structures. The long and short fiber self-assembled structure alone cannot achieve the performance described in the present invention, and the short fiber network structure alone with a large amount of cellulose film interspersed therein is directly broken during the washing process. The long and short fibers form a spatial network structure autonomously, and the dissolved cellulose is filled in the network structure. The ground film is formed by solution casting, and the ground film is solidified and finally shaped by solvent evaporation. Then, the physical structure and performance of the ground film are improved by surface sizing, and vacuum extrusion and drying are used to prepare a cellulose-based degradable agricultural ground film with a "reinforced concrete" structure.

[0030] (3) Excellent performance: The prepared corrugated paper-based biodegradable mulch film has excellent performance in key indicators such as quantity, thickness, tensile strength, tear resistance, burst resistance, and folding resistance, fully meeting the use requirements of agricultural mulch films. In addition, it also has good heat preservation and moisture retention effects, can effectively increase soil temperature and moisture content, and promote crop growth.

[0031] (4) Degradability: The mulch prepared by the present invention has good biodegradability. Whether it is applied on the surface or buried in the soil, it can achieve a high degradation rate within a certain period of time. This not only avoids the "white pollution" caused by the long-term residual soil of traditional plastic mulch, but also contributes to the healthy cycle of the soil ecosystem. The composting degradation test also further confirmed its excellent biodegradability and met environmental protection requirements.

[0032] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail the exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.

[0034] Figure 1 This is the microstructure diagram of the undegummed and deinked corrugated paper short fiber mulch.

[0035] Figure 2 This is the microstructure diagram of the degummed and deinked corrugated paper short fiber mulch.

[0036] Figure 3 This is the microstructure diagram of the de-inked corrugated paper with added cotton linter pulp film.

[0037] Figure 4 This is the microstructure diagram of degummed and deinked corrugated paper with low dosage of long fiber mulch added.

[0038] Figure 5 It is a mulch product and microstructure diagram of degummed and deinked corrugated paper with an appropriate amount of long fibers added but the disintegration time is too long.

[0039] Figure 6 This is the thermal insulation and moisture retention performance diagram of corrugated paper mulch with 10% long fiber content.

[0040] Figure 7 This is a graph showing the degradation performance of corrugated paper mulch with 10% long fiber content.

[0041] Figure 8 This is the "reinforced concrete" microstructure diagram of the corrugated paper mulch with 10% long fiber content.

[0042] Fig. 9 This is a picture of the fifth day of indoor planting of Chinese cabbage using a corrugated paper mulch film with a 10% dosage of long fibers according to Example 1.

[0043] Fig.10 This is a graph showing the thermal insulation and moisture retention performance of 8% gelatin mulch.

[0044] Fig.11This is a macroscopic morphology diagram of the natural degradation of 8% gelatin mulch.

[0045] Fig.12 The figure shows the natural degradation and composting degradation rates of 8% gelatin mulch.

[0046] Fig.13 This is a graph showing the thermal insulation and moisture retention performance of 1.25% paraffin emulsion mulch.

[0047] Fig.14 This is a graph showing the degradation performance of 1.25% paraffin emulsion mulch.

[0048] Fig.15 This is the thermal insulation and moisture retention performance diagram of 9% phosphate starch mulch.

[0049] Fig.16 This is a graph showing the degradation performance of 9% phosphate starch mulch.

[0050] Fig.17 This is the thermal insulation and moisture retention performance diagram of 0.7% PAM mulch.

[0051] Fig.18 This is the macroscopic morphology of the natural degradation of 0.7% PAM mulch applied on the surface.

[0052] Fig.19 This is the macroscopic morphology of the natural degradation of the 5cm tillage layer of 0.7% PAM mulch buried in the soil.

[0053] Fig. 20 This is a graph of the natural degradation and composting degradation rates of 0.7% PAM mulch.

[0054] Fig.21 This is the thermal insulation and moisture retention performance chart of 4% glycerol mulch.

[0055] Fig. 22 This is a graph of the degradation performance of 4% glycerol mulch.

[0056] Fig.23 This is the thermal insulation and moisture retention performance diagram of 3% cationic dispersed rosin glue mulch.

[0057] Fig.24 This is the degradation performance diagram of 43% cationic dispersed rosin glue mulch. DETAILED DESCRIPTION

[0058] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.

[0059] Corrugated paper fibers contain 57% cellulose, 11% hemicellulose, and 15% lignin. The cellulose content is much higher than that of grass, wood and other plant fibers (-42%), while the content of lignin and hemicellulose is much lower than those of these plant raw materials (lignin: -22%; hemicellulose: -28%). It is an ideal raw material for preparing cellulose-based biodegradable mulch.

[0060] Based on the above considerations, this patent innovatively proposes to use corrugated paper with low recycling value as raw material, learn from the hydrogen bond breaking mechanism of natural polymer cellulose, and use chemical means to disassemble and reactivate the hydrogen bonds in the fiber, so that the originally closed fiber pores can be reopened. At the same time, by disassembling the co-crystallized cellulose, the swelling performance and softness of the fiber are significantly improved. In this process, we also cleverly used alkali / urine solution to partially dissolve the low-polymerization cellulose on the surface of the corrugated paper fiber. To further optimize the performance, we mixed an appropriate amount of long fibers, such as Simao pine fibers, into the slurry, and then used a solution casting process to form and solidify the mulch. In the end, we successfully prepared a cellulose-based agricultural mulch film with a "reinforced concrete" structure, in which long and short fibers are staggered to form a network skeleton, and the cellulose film cleverly fills the network space, thereby preparing a biodegradable agricultural mulch film.

[0061] In order to better highlight the advantages and effects of the present invention, the present invention is further described in detail below through comparative examples and embodiments, but the protection scope of the present invention is not limited to the contents.

[0062] Example 1: Non-sizing mulch film with appropriate amount of long fibers added to degummed and deinked corrugated paper fibers

[0063] The present invention provides a method for preparing a cellulose-based biodegradable agricultural mulch film using low-recycling value corrugated paper as follows:

[0064] (1) Corrugated paper boxes / boards with low recycling value are broken into small paper scraps by a paper shredder, and 40 g of corrugated paper is added to a 2 L beaker according to the ratio of corrugated paper scraps: sodium hydroxide: water (g:g:ml) 4:6:300, and soaked for 24 h at room temperature. The mixture is transferred to an ultrasonic instrument with a frequency of 40 kHz and ultrasonicated for 1 h at an ultrasonic power of 100% and 80°C. During the process, the glue and ink foam floating on the surface are manually scraped off by a scraper. After degumming and deinking, the pulp is transferred to a 200 mesh pulp bag and centrifuged in a dehydrating spin dryer to obtain degummed and deinked corrugated paper pulp fibers.

[0065] (2) The commercially available long-fiber raw pulp board Simao pine pulp board was broken into small pieces by a paper shredder, 10 g of the shredded pulp board fiber was weighed and added to 500 g of softened tap water, and soaked at room temperature for 6 h. The fiber bundles were mechanically stirred at a speed of 2000 rpm for 5 min to dissociate the fiber bundles. After the dissociation was completed, the fiber bundles were transferred to a 200-mesh pulp bag and centrifuged using a dehydrating dryer to obtain the dissociated long-fiber wet pulp.

[0066] (3) Based on the theoretical mass of each mulch film being 2.21 g (based on absolute dry fiber), the long fiber wet slurry described in the above step (2) is weighed at 8%, 10%, 12%, 14%, 16%, and 20% by mass, and added to 100 g of a 7% sodium hydroxide / 12% urea aqueous solution precooled to -13°C, respectively. The mixture is mechanically stirred at a speed of 2000 rpm at room temperature for 4 min. After the stirring, 2.0332 g, 1.989 g, 1.9448 g, 1.9006 g, 1.8564 g, 1.8122 g, and 1.768 g (based on absolute dry fiber) of the degummed and deinked corrugated pulp fibers of step (1) are added, and the stirring is continued for 1 min to obtain a viscous mixed slurry in which the long and short fibers are evenly distributed and the fibers are filled with cellulose solution.

[0067] (4) The heterogeneous mixed viscous solution obtained in step (3) was poured into a transparent acrylic mold with an inner diameter of 19.2 cm×19.2 cm, and oscillated on a horizontal rotary oscillator at a speed of 200 rpm for 5 minutes to allow the solution to be cast, defoamed, and flattened. The long and short fibers were disorderly self-assembled and the cellulose solution evenly penetrated the fiber network structure. Then, the mulch was placed in an oven at 60°C for 6 hours to solidify the mulch film by solvent evaporation. After the film was formed, it was taken out and cooled to room temperature. Then, 200 ml of 7% ammonium sulfate solution was poured into the mulch to further reconstruct the hydrogen bonds of the cellulose. After standing for 5 minutes, the hydrogen bond reconstruction solution was poured out, and 100 ml of softened tap water was poured into it and soaked for 5 minutes (this operation was repeated 10-12 times) to remove the sodium hydroxide and urea in the sample until the sample was neutral. Then the wet film was laid flat between two filter cloths, and absorbent felt was placed on both sides. A large amount of moisture was removed from the wet film by rolling it back and forth with a roller, and then it was placed in a vacuum flat plate dryer preheated to 95°C and dried for 5 minutes to obtain a corrugated paper-based biodegradable film. The microstructure of the prepared biodegradable film was characterized by SEM, such as Figure 6As shown. Compared with the untreated raw fiber, the unit fiber treated by the above method becomes full and has no wrinkles on the surface; secondly, the ground film structure changes from a disordered stacking state to a more ordered woven structure, and the cellulose film runs through it, forming a complex network composed of single full fibers, which is similar to the reinforcement effect of reinforced concrete. At the same time, N2 adsorption and desorption and FTIR were used to determine the pore structure and crystallinity of the raw material and the ground film prepared by this patent, as shown in Table 1. As can be seen from Table 1, after the corrugated paper fiber is treated by this patent, the fiber specific surface area increases by 10%, the pore volume and average pore size increase by 60% and 11% respectively, and the crystallinity decreases by 20%.

[0068] Table 1 Pore structure and crystallinity of corrugated paper raw materials and fibers treated by the present invention

[0069] (5) The corrugated paper-based biodegradable mulch prepared in the above step (4) was tested for its quantitative weight, thickness, tensile strength, tear strength, burst resistance, folding resistance and water vapor barrier properties according to national standards GB / T 451.2-2002, GB / T451.3-2002, GB / T 455-2002, GB / T 454-2020, GB / T 12914-2018, GB / T 457-2018 and GB-T1037-2021. The test results are shown in Table 2.

[0070] Table 2 Physical properties of corrugated paper mulch with different long fiber content

[0071] (6) The corrugated paper mulch prepared in step (4) above with a 10% dosage of long fibers was cut into 17 cm × 17 cm pieces and placed in a constant temperature and humidity chamber at a relative humidity of (50±2)% and a temperature of (23±1)°C for 24 hours. The heat preservation and moisture retention effect was measured in a 5-gallon flower pot filled with 10 kg of red sandy soil with a saturated moisture content of 40% and a weak acidity (pH = 5.7). The mulch was taken out after balancing and spread on the soil surface with a humidity of 40%. The soil with the same humidity was then placed around the mulch. The soil temperature at 5 cm and 10 cm tillage layer was measured on the day of mulch film laying, 7 days, 14 days, 21 days, 28 days, 35 days, 42 days, 49 days, 56 days and 63 days respectively. After the temperature collection, the soil at 5 cm tillage layer and 10 cm tillage layer was taken respectively, and the soil moisture content was measured by drying method. In order to compare the effects, a control group (plastic mulch film covering and no covering) was made. The heat preservation and moisture retention effect of the corrugated paper mulch with 10% long fiber was shown in Figure 2. Figure 7 .

[0072] (7) Determine the biodegradability of the corrugated paper mulch prepared in step (4) above with a 10% long fiber dosage. Surface application degradation: After the temperature measurement in step (6) above is completed, carefully peel off the surface mulch and use a brush to sweep away the soil on the surface. Then use softened tap water to repeatedly clean the surface soil, and then place it on a 95°C vacuum flat plate dryer to dry for 5 minutes. Take it out and place it under relative humidity (50±2)% and temperature (23±1)°C for 24 hours for equilibrium. Then weigh it. The surface application degradation rate is calculated based on the ratio of the mass difference of the mulch before and after application to the mass of the mulch before degradation. Soil burial degradation: Cut the corrugated paper mulch with a 10% long fiber dosage into 16cm×16cm pieces and spread it on a 5cm tillage layer. Attach soil with the same humidity. Take out the mulch samples 7 days, 14 days, 21 days, 28 days, 35 days, 42 days, 49 days, 56 days and 63 days after the mulch is buried in the soil to determine its soil burial degradation rate. Figure 8 It is the degradation rate and macroscopic characteristics of mulch film.

[0073] (8) The mulch with a long fiber dosage of 16% was used for indoor planting of Chinese cabbage. Three 5-gallon plastic flower pots were taken, and the soil was poor red soil. The humidity was controlled at 30% and no fertilizer was applied. The paper mulch prepared by the solution casting method (No. 1) was covered, the commercially available plastic mulch (No. 2) was covered, and the mulch was not covered (No. 3). On the first day after sowing, No. 2 began to sprout, No. 1 had a small number of sprouts, and No. 3 showed no change. On the second day, all No. 2 sprouted, and the seeds began to appear petal-shaped. No. 1 and No. 3 all sprouted, but No. 1 sprouted significantly and grew better than No. 3. On the fourth day, the two groups of covered cabbage began to grow and the top film state appeared. We artificially broke the film. The way to break the homemade paper mulch was to puncture and moisten the top film with a syringe, and the plastic mulch was opened by hand. The blank group began to show yellowing of tender shoots compared with the covered group. On the fifth day of cabbage growth, there was a difference in plant height. Plant No. 1 is about 3 cm tall, plant No. 2 is about 2 cm tall, and plant No. 3 is only about 1 cm tall. Fig. 9 shown.

[0074] Example 2: Degummed and deinked corrugated paper fiber with 12% long fiber gelatin sizing film

[0075] The present invention provides a method for preparing a cellulose-based biodegradable agricultural mulch film using low-recycling value corrugated paper as follows:

[0076] (1) Corrugated paper boxes / boards with low recycling value are broken into small paper scraps by a paper shredder. 30g of corrugated paper is added into a 1L beaker according to the ratio of corrugated paper scraps: sodium hydroxide: water (g:g:ml) 3:4.5:225, and soaked for 24h at room temperature. Then, the paper is transferred to an ultrasonic instrument with a frequency of 100kHz and ultrasonicated at 80°C for 1h under the condition of 100% ultrasonic power. During the process, the glue and ink foam floating on the surface are manually scraped off by a scraper. After degumming and deinking, the pulp is transferred to a 200-mesh pulp bag and centrifuged by a dehydrating spin dryer to obtain degummed and deinked corrugated paper pulp fiber.

[0077] (2) The commercially available long-fiber raw pulp board Simao pine pulp board was broken into small pieces by a paper shredder, 15 g of the shredded pulp board fiber was weighed and added to 750 g of softened tap water, and soaked at room temperature for 6 h. The fiber bundles were mechanically stirred at a speed of 2000 rpm for 5 min to dissociate the fiber bundles. After the dissociation was completed, the fiber bundles were transferred to a 200-mesh pulp bag and centrifuged in a dehydrating spin dryer to obtain the dissociated long-fiber wet pulp.

[0078] (3) Weigh 0.2652 g (based on absolute dry fiber) of the long fiber wet pulp described in step (2) above, add it to 100 g of 7% sodium hydroxide / 12% urea aqueous solution that has been precooled to -13°C, and mechanically stir at 2000 rpm for 4 min at room temperature. After stirring, add 1.9448 g (based on absolute dry fiber) of the degummed and deinked corrugated pulp fiber of step (1), and continue stirring for 1 min to obtain a viscous mixed slurry in which the long and short fibers are evenly distributed and the spaces between the fibers are filled with cellulose solution.

[0079] (4) Pour the heterogeneous mixed viscous solution obtained in step (3) into a transparent acrylic mold with an inner diameter of 19.2 cm×19.2 cm, and oscillate on a horizontal rotary oscillator at a speed of 200 rpm for 8 minutes to allow the solution to be cast, defoamed, and flattened. The long and short fibers are disorderly self-assembled and the cellulose solution evenly penetrates the fiber network structure. Then, the mold is placed in an oven at 60°C for 6 hours to solidify the mulch film by solvent evaporation. After the film is formed, take it out and cool it to room temperature. Then, pour in 200 ml of 7% ammonium sulfate solution to further reconstruct the hydrogen bonds of the cellulose. After standing for 5 minutes, pour out the hydrogen bond reconstruction solution, pour in 100 ml of softened tap water and soak for 5 minutes (this operation is repeated 12 times) to remove the sodium hydroxide and urea in the sample until the sample is neutral. The wet film is then spread flat between two filter cloths, and absorbent felt is placed on both sides. A large amount of moisture on the wet film is removed by rolling back and forth with a pressure roller, and 5 ml of 10 ml gelatin aqueous solution with a concentration of 2%, 4%, 6%, 8%, 10%, 12%, and 16% (based on the calculated mass of each piece of film) is evenly coated on both sides of the film by a coating process and allowed to stand for 10 minutes. It is then placed in a vacuum flat plate dryer preheated to 95°C and dried for 5 minutes to obtain gelatin-coated corrugated paper-based biodegradable film.

[0080] (5) The mulch films with different gelatin application amounts prepared in the above step (4) were tested for their quantitative properties, thickness, tensile strength, tear strength, burst resistance, folding resistance and water vapor barrier properties according to national standards GB / T 451.2-2002, GB / T451.3-2002, GB / T 455-2002, GB / T 454-2020, GB / T 12914-2018, GB / T 457-2018 and GB-T1037-2021. The test results are shown in Table 3.

[0081] Table 3 Physical properties of different gelatin mulch films

[0082] (6) Cut the 8% gelatin mulch prepared in step (4) into 17 cm × 17 cm pieces and place them in a constant temperature and humidity chamber at a relative humidity of (50±2)% and a temperature of (23±1)°C for 24 hours. The heat preservation and moisture retention effect is measured in a 5-gallon flower pot filled with 10 kg of red sandy soil with a saturated moisture content of 40% and a weak acidity (pH = 5.7). Take out the equilibrated mulch and spread it on the soil surface with a humidity of 40%. Cover it with soil of the same humidity on all sides. The soil was covered with plastic mulch, and then the soil temperature at 5 cm and 10 cm tillage layer was measured on the day of mulch film laying, 7 days, 14 days, 21 days, 28 days, 35 days, 42 days, 49 days, 56 days and 63 days. After the temperature collection was completed, the soil at 5 cm tillage layer and 10 cm tillage layer was taken respectively, and the soil moisture content was determined by drying method. In order to compare the effects, a control group (plastic mulch covering and no covering) was made. The heat preservation and moisture retention effect of applying 8% gelatin mulch is shown in Figure 2. Fig.10 .

[0083] (7) Determine the biodegradability of the 8% gelatin application rate prepared in step (4) above. Compost biodegradation: Compost degradation was determined in accordance with the national standard GB / T 19277.1-2011. Surface application degradation: After the temperature determination in step (6) above was completed, carefully remove the surface film and sweep away the surface soil with a brush, then repeatedly clean the surface soil with softened tap water, and then place it on a 95°C vacuum flat plate dryer to dry for 5 minutes, take it out and place it under relative humidity (50±2)% and temperature (23±1)°C for 24 hours, then weigh it, and calculate the surface application degradation rate based on the ratio of the mass difference of the film before and after application to the mass of the film before degradation. Soil burial degradation: Cut the glycerol mulch into 16cm×16cm pieces and spread them on the 5cm tillage layer. Then add soil with the same humidity. Take out the mulch samples at 7, 14, 21, 28, 35, 42, 49, 56 and 63 days after the mulch was buried in the soil to determine its soil burial degradation rate. Fig.11 Macroscopic characteristics of mulch film degradation. Fig.12It is the natural degradation rate of mulch and the degradation situation of composting.

[0084] Example 3: Degummed and deinked corrugated paper fiber with 16% long fiber paraffin emulsion sizing film

[0085] The present invention provides a method for preparing a cellulose-based biodegradable agricultural mulch film using low-recycling value corrugated paper as follows:

[0086] (1) Corrugated paper boxes / boards with low recycling value are broken into small paper scraps by a paper shredder. 20g of corrugated paper is added into a 500ml beaker according to the ratio of corrugated paper scraps: sodium hydroxide: water (g:g:ml) 2:3:150, and soaked for 24h at room temperature. Then, the paper is transferred to an ultrasonic instrument with a frequency of 80kHz and ultrasonicated at 80°C for 1h under the condition of 100% ultrasonic power. During the process, the glue and ink foam floating on the surface are manually scraped off by a scraper. After degumming and deinking, the pulp is transferred to a 200-mesh pulp bag and centrifuged by a dehydrating spin dryer to obtain degummed and deinked corrugated paper pulp fibers.

[0087] (2) The commercially available long-fiber raw pulp board Simao pine pulp board was broken into small pieces by a paper shredder, 10 g of the shredded pulp board fiber was weighed and added to 500 g of softened tap water, and soaked at room temperature for 6 h. The fiber bundles were mechanically stirred at a speed of 2000 rpm for 5 min to dissociate the fiber bundles. After the dissociation was completed, the fiber bundles were transferred to a 200-mesh pulp bag and centrifuged using a dehydrating dryer to obtain the dissociated long-fiber wet pulp.

[0088] (3) Weigh 0.3536 g (based on absolute dry fiber) of the long fiber wet pulp described in step (2) above, add it to 100 g of 7% sodium hydroxide / 12% urea aqueous solution that has been precooled to -13°C, and mechanically stir at 2000 rpm for 4 min at room temperature. After stirring, add 1.8564 g (based on absolute dry fiber) of the degummed and deinked corrugated pulp fiber of step (1), and continue stirring for 1 min to obtain a viscous mixed slurry in which the long and short fibers are evenly distributed and the fibers are filled with cellulose solution.

[0089] (4) Pour the heterogeneous mixed viscous solution obtained in step (3) into a transparent acrylic mold with an inner diameter of 19.2 cm×19.2 cm, and oscillate on a horizontal rotary oscillator at a speed of 200 rpm for 5 minutes to allow the solution to be cast, defoamed, and flattened. The long and short fibers are disorderly self-assembled and the cellulose solution evenly penetrates the fiber network structure. Then, the mold is placed in an oven at 60°C for 6 hours to solidify the mulch film by solvent evaporation. After the film is formed, take it out and cool it to room temperature. Then, pour in 200 ml of 7% ammonium sulfate solution to further reconstruct the hydrogen bonds of the cellulose. After standing for 5 minutes, pour out the hydrogen bond reconstruction solution, pour in 100 ml of softened tap water and soak for 5 minutes (this operation is repeated 10-12 times) to remove the sodium hydroxide and urea in the sample until the sample is neutral. The wet film is then spread flat between two filter cloths, absorbent felt is placed on both sides, and a large amount of moisture on the wet film is removed by rolling back and forth with a pressure roller. 5 ml of 10 ml of paraffin emulsion aqueous solution with concentrations of 0.25%, 0.5%, 0.75%, 1.0%, 1.25%, 1.5%, and 1.75% (based on the calculated mass of each piece of film) is evenly coated on both sides of the film by a coating process and allowed to stand for 10 minutes. Then, it is placed in a vacuum flat dryer preheated to 95°C and dried for 5 minutes to obtain the paraffin emulsion glued corrugated paper-based biodegradable film.

[0090] (5) The mulch films with different application amounts of paraffin emulsion prepared in the above step (4) were tested for their quantitative properties, thickness, tensile strength, tear strength, burst resistance, folding resistance and water vapor barrier properties according to national standards GB / T451.2-2002, GB / T 451.3-2002, GB / T 455-2002, GB / T 454-2020, GB / T 12914-2018, GB / T457-2018 and GB-T1037-2021. The test results are shown in Table 4.

[0091] Table 4 Physical properties of mulch films applied with different paraffin emulsions

[0092] (6) Cut the mulch film prepared in step (4) above with an application amount of 1.25% paraffin emulsion into 17 cm × 17 cm pieces and place them in a constant temperature and humidity chamber at a relative humidity of (50±2)% and a temperature of (23±1)°C for 24 hours. The heat preservation and moisture retention effect is measured in a 5-gallon flower pot filled with 10 kg of red sandy soil with a saturated moisture content of 40% and a weak acidity (pH = 5.7): take out the mulch film after balancing and spread it on the soil surface with a humidity of 40%, and surround it with soil with the same humidity. The soil was covered with plastic film, and then the soil temperature at 5 cm and 10 cm tillage layer was measured on the day of film laying, 7 days, 14 days, 21 days, 28 days, 35 days, 42 days, 49 days, 56 days and 63 days. After the temperature collection was completed, the soil at 5 cm tillage layer and 10 cm tillage layer was taken respectively, and the soil moisture content was determined by drying method. In order to compare the effects, a control group (plastic film covering and no covering) was made. The heat preservation and moisture retention effect of applying 1.25% paraffin emulsion film is shown in Figure 2. Fig.13 .

[0093] (7) Determine the biodegradability of the 1.25% paraffin emulsion prepared in step (4) above. Surface application degradation: After the temperature measurement in step (6) above is completed, carefully peel off the surface film and use a brush to sweep away the soil on the surface. Then use softened tap water to repeatedly clean the surface soil, and then place it on a 95°C vacuum flat plate dryer to dry for 5 minutes. Take it out and place it under relative humidity (50±2)% and temperature (23±1)°C for 24 hours to balance it. Then weigh it. The surface application degradation rate is calculated based on the ratio of the mass difference of the film before and after application to the mass of the film before degradation. Soil burial degradation: Cut the film into 16cm×16cm pieces and spread it on a 5cm tillage layer. Attach soil with the same humidity. Take out the film samples 7 days, 14 days, 21 days, 28 days, 35 days, 42 days, 49 days, 56 days and 63 days after the film is buried in the soil to determine its soil burial degradation rate. Fig.14 It is the degradation rate and macroscopic characteristics of mulch film.

[0094] Example 4: Degummed and deinked corrugated paper fiber with 16% long fiber phosphate starch sizing film

[0095] The present invention provides a method for preparing a cellulose-based biodegradable agricultural mulch film using low-recycling value corrugated paper as follows:

[0096] (1) Corrugated paper boxes / boards with low recycling value are broken into small paper scraps by a paper shredder. 20g of corrugated paper is added into a 500ml beaker according to the ratio of corrugated paper scraps: sodium hydroxide: water (g:g:ml) 2:3:150, and soaked for 24h at room temperature. Then, the paper is transferred to an ultrasonic instrument with a frequency of 80kHz and ultrasonicated at 80°C for 1h under the condition of 100% ultrasonic power. During the process, the glue and ink foam floating on the surface are manually scraped off by a scraper. After degumming and deinking, the pulp is transferred to a 200-mesh pulp bag and centrifuged by a dehydrating spin dryer to obtain degummed and deinked corrugated paper pulp fibers.

[0097] (2) The commercially available long-fiber raw pulp board Simao pine pulp board was broken into small pieces by a paper shredder, 10 g of the shredded pulp board fiber was weighed and added to 500 g of softened tap water, and soaked at room temperature for 6 h. The fiber bundles were mechanically stirred at a speed of 2000 rpm for 5 min to dissociate the fiber bundles. After the dissociation was completed, the fiber bundles were transferred to a 200-mesh pulp bag and centrifuged using a dehydrating dryer to obtain the dissociated long-fiber wet pulp.

[0098] (3) Weigh 0.3536 g (based on absolute dry fiber) of the long fiber wet pulp described in step (2) above, add it to 100 g of 7% sodium hydroxide / 12% urea aqueous solution that has been precooled to -13°C, and mechanically stir at 2000 rpm for 4 min at room temperature. After stirring, add 1.8564 g (based on absolute dry fiber) of the degummed and deinked corrugated pulp fiber of step (1), and continue stirring for 1 min to obtain a viscous mixed slurry in which the long and short fibers are evenly distributed and the fibers are filled with cellulose solution.

[0099] (4) Pour the heterogeneous mixed viscous solution obtained in step (3) into a transparent acrylic mold with an inner diameter of 19.2 cm×19.2 cm, and oscillate on a horizontal rotary oscillator at a speed of 200 rpm for 5 minutes to allow the solution to be cast, defoamed, and flattened. The long and short fibers are disorderly self-assembled and the cellulose solution evenly penetrates the fiber network structure. Then, the mold is placed in an oven at 60°C for 6 hours to solidify the mulch film by solvent evaporation. After the film is formed, take it out and cool it to room temperature. Then, pour in 200 ml of 7% ammonium sulfate solution to further reconstruct the hydrogen bonds of the cellulose. After standing for 5 minutes, pour out the hydrogen bond reconstruction solution, pour in 100 ml of softened tap water and soak for 5 minutes (this operation is repeated 10-12 times) to remove the sodium hydroxide and urea in the sample until the sample is neutral. The wet film is then spread flat between two filter cloths, and absorbent felt is placed on both sides. A large amount of moisture on the wet film is removed by rolling back and forth with a pressure roller, and 5 ml of 10 ml of phosphate starch aqueous solution (based on the calculated mass of each piece of film) with concentrations of 5.0%, 7.0%, 9.0%, 11.0%, 13.0%, 15.0%, and 17.0% are respectively evenly coated on both sides of the film by a coating process and allowed to stand for 10 minutes. Then, it is placed in a vacuum flat plate dryer preheated to 95°C and dried for 5 minutes to obtain the phosphate starch glue-coated corrugated paper-based biodegradable film.

[0100] (5) The mulch films with different application amounts of phosphate starch prepared in the above step (4) were tested for their quantitative properties, thickness, tensile strength, tear strength, burst resistance, folding resistance and water vapor barrier properties according to national standards GB / T451.2-2002, GB / T 451.3-2002, GB / T 455-2002, GB / T 454-2020, GB / T 12914-2018, GB / T457-2018 and GB-T1037-2021. The test results are shown in Table 5.

[0101] Table 5 Physical properties of mulch films applied with different phosphate starches

[0102]

[0103] (6) Cut the mulch film with 9% phosphate starch application amount prepared in step (4) above into 17 cm × 17 cm pieces and place them in a constant temperature and humidity chamber with a relative humidity of (50±2)% and a temperature of (23±1)°C for 24 hours. The heat preservation and moisture retention effect is measured in a 5-gallon flower pot filled with 10 kg of red sandy soil with a saturated moisture content of 40% and a weak acidity (pH = 5.7): take out the mulch film after balancing and spread it on the soil surface with a humidity of 40%, and surround it with soil with the same humidity. The soil was covered with plastic film, and then the soil temperature at 5cm and 10cm tillage layer was measured on the day of film laying, 7th day, 14th day, 21st day, 28th day, 35th day, 42nd day, 49th day, 56th day and 63rd day. After the temperature collection, the soil at 5cm tillage layer and 10cm tillage layer was taken respectively, and the soil moisture content was determined by drying method. In order to compare the effects, a control group (plastic film covering and no covering) was made. The heat preservation and moisture retention effect of applying 9% phosphate starch film is shown in Figure 2. Fig.15 .

[0104] (7) Determine the biodegradability of the 9% phosphate starch prepared in step (4) above. Surface application degradation: After the temperature measurement in step (6) above is completed, carefully peel off the surface film and use a brush to sweep away the soil on the surface. Then use softened tap water to repeatedly clean the surface soil, and then place it on a 95°C vacuum flat plate dryer to dry for 5 minutes. Take it out and place it under relative humidity (50±2)% and temperature (23±1)°C for 24 hours to balance it. Then weigh it. The surface application degradation rate is calculated based on the ratio of the mass difference of the film before and after application to the mass of the film before degradation. Soil burial degradation: Cut the film into 16cm×16cm pieces and spread it on a 5cm tillage layer. Attach soil with the same humidity. Take out the film samples 7 days, 14 days, 21 days, 28 days, 35 days, 42 days, 49 days, 56 days and 63 days after the film is buried in the soil to determine its soil burial degradation rate. Fig.16 It is the degradation rate and macroscopic characteristics of mulch film.

[0105] Example 5: PAM sizing film with 12% long fiber added to degummed and deinked corrugated paper fiber

[0106] The present invention provides a method for preparing a cellulose-based biodegradable agricultural mulch film using low-recycling value corrugated paper as follows:

[0107] (1) Corrugated paper boxes / boards with low recycling value are broken into small paper scraps by a paper shredder. 30g of corrugated paper is added into a 1L beaker according to the ratio of corrugated paper scraps: sodium hydroxide: water (g:g:ml) 3:4.5:225, and soaked for 24h at room temperature. Then, the paper is transferred to an ultrasonic instrument with a frequency of 120kHz and ultrasonicated for 40min at 7°C under the condition of 80% ultrasonic power. During the process, the glue and ink foam floating on the surface are manually scraped off by a scraper. After degumming and deinking, the pulp is transferred to a 200-mesh pulp bag and centrifuged by a dehydrating spin dryer to obtain degummed and deinked corrugated paper pulp fibers.

[0108] (2) The commercially available long-fiber raw pulp board Simao pine pulp board was broken into small pieces by a paper shredder, 10 g of the shredded pulp board fiber was weighed and added to 500 g of softened tap water, and soaked at room temperature for 6 h. The fiber bundles were mechanically stirred at a speed of 2000 rpm for 5 min to dissociate the fiber bundles. After the dissociation was completed, the fiber bundles were transferred to a 200-mesh pulp bag and centrifuged using a dehydrating dryer to obtain the dissociated long-fiber wet pulp.

[0109] (3) Weigh 0.2652 g (based on absolute dry fiber) of the long fiber wet pulp described in step (2) above, add it to 100 g of 7% sodium hydroxide / 12% urea aqueous solution that has been precooled to -13°C, and mechanically stir at 2000 rpm for 4 min at room temperature. After stirring, add 1.9448 g (based on absolute dry fiber) of the degummed and deinked corrugated pulp fiber of step (1), and continue stirring for 1 min to obtain a viscous mixed slurry in which the long and short fibers are evenly distributed and the spaces between the fibers are filled with cellulose solution.

[0110] (4) Pour the heterogeneous mixed viscous solution obtained in step (3) into a transparent acrylic mold with an inner diameter of 19.2 cm×19.2 cm, and oscillate on a horizontal rotary oscillator at a speed of 200 rpm for 5 minutes to allow the solution to be cast, defoamed, and flattened. The long and short fibers are disorderly self-assembled and the cellulose solution evenly penetrates the fiber network structure. Then, the mold is placed in an oven at 60°C for 6 hours to solidify the mulch film by solvent evaporation. After the film is formed, take it out and cool it to room temperature. Then, pour in 200 ml of 7% ammonium sulfate solution to further reconstruct the hydrogen bonds of the cellulose. After standing for 5 minutes, pour out the hydrogen bond reconstruction solution, pour in 100 ml of softened tap water and soak for 5 minutes (this operation is repeated 12 times) to remove the sodium hydroxide and urea in the sample until the sample is neutral. The wet film is then spread flat between two filter cloths, absorbent felt is placed on both sides, and a large amount of moisture on the wet film is removed by rolling back and forth with a pressure roller. 5 ml of 10 ml PAM aqueous solution (based on the calculated mass of each piece of film) with concentrations of 0.1%, 0.3%, 0.5%, 0.7%, 1.0%, 1.2%, and 1.5% are respectively evenly coated on both sides of the film by a coating process and allowed to stand for 10 minutes. Then, it is placed in a vacuum flat plate dryer preheated to 95°C and dried for 5 minutes to obtain gelatin-coated corrugated paper-based biodegradable film.

[0111] (5) The mulch films with different gelatin application amounts prepared in the above step (4) were tested for their quantitative properties, thickness, tensile strength, tear strength, burst resistance, folding resistance and water vapor barrier properties according to national standards GB / T 451.2-2002, GB / T451.3-2002, GB / T 455-2002, GB / T 454-2020, GB / T 12914-2018, GB / T 457-2018 and GB-T1037-2021. The test results are shown in Table 6.

[0112] Table 6 Physical properties of mulch films applied with different PAMs

[0113] (6) The mulch film with 0.7% PAM application rate prepared in step (4) above was cut into 17 cm × 17 cm pieces and placed in a constant temperature and humidity chamber with a relative humidity of (50±2)% and a temperature of (23±1)°C for 24 hours. The heat preservation and moisture retention effect was measured in a 5-gallon flower pot filled with 10 kg of red sandy soil with a saturated moisture content of 40% and a weak acidity (pH = 5.7): the mulch film after equilibration was taken out and spread on the soil surface with a humidity of 40%, and the soil with the same humidity was used on all sides. The soil was covered with plastic film, and then the soil temperature at 5 cm and 10 cm tillage layer was measured on the day of film laying, 7 days, 14 days, 21 days, 28 days, 35 days, 42 days, 49 days, 56 days and 63 days. After the temperature collection was completed, the soil at 5 cm tillage layer and 10 cm tillage layer was taken respectively, and the soil moisture content was measured by drying method. In order to compare the effects, a control group (plastic film covering and no covering) was made. The heat preservation and moisture retention effect of applying 0.7% PAM film is shown in Figure 2. Fig.17 .

[0114] (7) Determine the biodegradability of the 0.7% PAM prepared in step (4). Compost biodegradation: Compost degradation was determined in accordance with the national standard GB / T 19277.1-2011. Surface application degradation: After the temperature determination in step (6) was completed, carefully remove the surface film and sweep away the soil on the surface with a brush, then repeatedly clean the surface soil with softened tap water, and then place it on a 95°C vacuum flat plate dryer to dry for 5 minutes, take it out and place it under relative humidity (50±2)% and temperature (23±1)°C for 24 hours, then weigh it, and calculate the surface application degradation rate based on the ratio of the mass difference of the film before and after application to the mass of the film before degradation. Soil burial degradation: Cut the glycerol mulch into 16cm×16cm pieces and spread them on the 5cm tillage layer. Then add soil with the same humidity. Take out the mulch samples at 7, 14, 21, 28, 35, 42, 49, 56 and 63 days after the mulch was buried in the soil to determine its soil burial degradation rate. Fig.18 Macroscopic characteristics of degradation of mulch surface, Fig.19 The macroscopic characteristics of the degradation of the 5cm tillage layer buried in the mulch are shown in Figure 1. Fig. 20 It is the natural degradation rate of mulch and the degradation situation of composting.

[0115] Example 6: Degummed and deinked corrugated paper fiber with 16% long fiber glycerin sizing film

[0116] The present invention provides a method for preparing a cellulose-based biodegradable agricultural mulch film using low-recycling value corrugated paper as follows:

[0117] (1) Corrugated paper boxes / boards with low recycling value are broken into small paper scraps by a paper shredder, and 20g of corrugated paper is added to a 1L beaker according to the ratio of corrugated paper scraps: sodium hydroxide: water (g:g:ml) 2:3:150, and soaked for 24 hours at room temperature, and then transferred to an ultrasonic instrument with a frequency of 40kHz, and ultrasonicated at 80°C for 1 hour under the condition of 100% ultrasonic power. During the process, the glue and ink foam floating on the surface are manually scraped off with a scraper. After degumming and deinking, the slurry is transferred to a 200-mesh pulp bag and centrifuged in a dehydrating spin dryer to obtain degummed and deinked corrugated paper pulp fibers.

[0118] (2) The commercially available long-fiber raw pulp board Simao pine pulp board was broken into small pieces by a paper shredder, 10 g of the shredded pulp board fiber was weighed and added to 500 g of softened tap water, and soaked at room temperature for 6 h. The fiber bundles were mechanically stirred at a speed of 2000 rpm for 5 min to dissociate the fiber bundles. After the dissociation was completed, the fiber bundles were transferred to a 200-mesh pulp bag and centrifuged using a dehydrating dryer to obtain the dissociated long-fiber wet pulp.

[0119] (3) Weigh 0.3536 g (based on absolute dry fiber) of the long fiber wet pulp described in step (2) above, add it to 100 g of 7% sodium hydroxide / 12% urea aqueous solution that has been precooled to -13°C, and mechanically stir at 2000 rpm for 4 min at room temperature. After stirring, add 1.8564 g (based on absolute dry fiber) of the degummed and deinked corrugated pulp fiber of step (1), and continue stirring for 1 min to obtain a viscous mixed slurry in which the long and short fibers are evenly distributed and the fibers are filled with cellulose solution.

[0120] (4) Pour the heterogeneous mixed viscous solution obtained in step (3) into a transparent acrylic mold with an inner diameter of 19.2 cm×19.2 cm, and oscillate on a horizontal rotary oscillator at a speed of 200 rpm for 5 minutes to allow the solution to be cast, defoamed, and flattened. The long and short fibers are disorderly self-assembled and the cellulose solution evenly penetrates the fiber network structure. Then, the mold is placed in an oven at 60°C for 6 hours to solidify the mulch film by solvent evaporation. After the film is formed, take it out and cool it to room temperature. Then, pour in 200 ml of 7% ammonium sulfate solution to further reconstruct the hydrogen bonds of the cellulose. After standing for 5 minutes, pour out the hydrogen bond reconstruction solution, pour in 100 ml of softened tap water and soak for 5 minutes (this operation is repeated 10-12 times) to remove the sodium hydroxide and urea in the sample until the sample is neutral. The wet film is then spread flat between two filter cloths, and absorbent felt is placed on both sides. A large amount of moisture on the wet film is removed by rolling back and forth with a pressure roller, and 5 ml of 10 ml glycerol aqueous solution with a concentration of 1%, 2%, 3%, 4%, 5%, 6%, and 7% (based on the calculated mass of each piece of film) is evenly coated on both sides of the film by a coating process and allowed to stand for 10 minutes. It is then placed in a vacuum flat plate dryer preheated to 95°C and dried for 5 minutes to obtain glycerin-sizing corrugated paper-based biodegradable film.

[0121] (5) The mulch films with different glycerol application amounts prepared in the above step (4) were tested for their quantitative properties, thickness, tensile strength, tear strength, burst resistance, folding resistance and water vapor barrier properties according to national standards GB / T 451.2-2002, GB / T451.3-2002, GB / T 455-2002, GB / T 454-2020, GB / T 12914-2018, GB / T 457-2018 and GB-T1037-2021. The test results are shown in Table 7.

[0122] Table 7 Physical properties of mulch films with different glycerol applications

[0123]

[0124]

[0125] (6) Cut the 4% glycerol mulch prepared in step (4) into 17 cm × 17 cm pieces and place them in a constant temperature and humidity chamber at a relative humidity of (50±2)% and a temperature of (23±1)°C for 24 hours. The heat preservation and moisture retention effect is measured in a 5-gallon flower pot filled with 10 kg of red sandy soil with a saturated moisture content of 40% and a weak acidity (pH = 5.7). Take out the equilibrated mulch and spread it on the soil surface with a humidity of 40%. The soil was covered, and then the soil temperature at the 5cm and 10cm tillage layers was measured on the day of mulch film laying, the 7th day, the 14th day, the 21st day, the 28th day, the 35th day, the 42nd day, the 49th day, the 56th day, and the 63rd day. After the temperature collection was completed, the soil at the 5cm tillage layer and the 10cm tillage layer was taken, and the soil moisture content was determined by the drying method. In order to compare the effects, a control group (plastic mulch covering and no covering) was made. The heat preservation and moisture retention effect of the glycerol mulch is shown in Figure 2. Fig.21 .

[0126] (7) Determine the biodegradability of the 4% glycerol application amount prepared in the above step (4). Surface application degradation: After the temperature measurement in the above step (6) is completed, carefully peel off the surface film and use a brush to sweep away the surface soil. Then use softened tap water to repeatedly clean the surface soil, and then place it on a 95℃ vacuum flat plate dryer to dry for 5 minutes. Take it out and place it under relative humidity (50±2)% and temperature (23±1)℃ for 24 hours to balance it. Then weigh it. The surface application degradation rate is calculated based on the ratio of the mass difference of the film before and after application to the mass of the film before degradation. Soil burial degradation: Cut the glycerol film into 16cm×16cm pieces and spread it on a 5cm tillage layer. Attach soil with the same humidity. Take out the film samples 7 days, 14 days, 21 days, 28 days, 35 days, 42 days, 49 days, 56 days and 63 days after the film is buried in the soil to determine its soil burial degradation rate. Fig. 22 It is the degradation rate and macroscopic characteristics of mulch film.

[0127] Example 7: Degummed and deinked corrugated paper fiber with 16% long fiber cationic dispersed rosin size for sizing ground film

[0128] The present invention provides a method for preparing a cellulose-based biodegradable agricultural mulch film using low-recycling value corrugated paper as follows:

[0129] (1) Corrugated paper boxes / boards with low recycling value are broken into small paper scraps by a paper shredder. 20g of corrugated paper is added into a 500ml beaker according to the ratio of corrugated paper scraps: sodium hydroxide: water (g:g:ml) 2:3:150, and soaked for 24h at room temperature. Then, the paper is transferred to an ultrasonic instrument with a frequency of 80kHz and ultrasonicated at 80°C for 1h under the condition of 100% ultrasonic power. During the process, the glue and ink foam floating on the surface are manually scraped off by a scraper. After degumming and deinking, the pulp is transferred to a 200-mesh pulp bag and centrifuged by a dehydrating spin dryer to obtain degummed and deinked corrugated paper pulp fibers.

[0130] (2) The commercially available long-fiber raw pulp board Simao pine pulp board was broken into small pieces by a paper shredder, 10 g of the shredded pulp board fiber was weighed and added to 500 g of softened tap water, and soaked at room temperature for 6 h. The fiber bundles were mechanically stirred at a speed of 2000 rpm for 5 min to dissociate the fiber bundles. After the dissociation was completed, the fiber bundles were transferred to a 200-mesh pulp bag and centrifuged using a dehydrating dryer to obtain the dissociated long-fiber wet pulp.

[0131] (3) Weigh 0.3536 g (based on absolute dry fiber) of the long fiber wet pulp described in step (2) above, add it to 100 g of 7% sodium hydroxide / 12% urea aqueous solution that has been precooled to -13°C, and mechanically stir at 2000 rpm for 4 min at room temperature. After stirring, add 1.8564 g (based on absolute dry fiber) of the degummed and deinked corrugated pulp fiber of step (1), and continue stirring for 1 min to obtain a viscous mixed slurry in which the long and short fibers are evenly distributed and the fibers are filled with cellulose solution.

[0132] (4) Pour the heterogeneous mixed viscous solution obtained in step (3) into a transparent acrylic mold with an inner diameter of 19.2 cm×19.2 cm, and oscillate on a horizontal rotary oscillator at a speed of 200 rpm for 5 minutes to allow the solution to be cast, defoamed, and flattened. The long and short fibers are disorderly self-assembled and the cellulose solution evenly penetrates the fiber network structure. Then, the mold is placed in an oven at 60°C for 6 hours to solidify the mulch film by solvent evaporation. After the film is formed, take it out and cool it to room temperature. Then, pour in 200 ml of 7% ammonium sulfate solution to further reconstruct the hydrogen bonds of the cellulose. After standing for 5 minutes, pour out the hydrogen bond reconstruction solution, pour in 100 ml of softened tap water and soak for 5 minutes (this operation is repeated 10-12 times) to remove the sodium hydroxide and urea in the sample until the sample is neutral. The wet film is then spread flat between two filter cloths, and absorbent felt is placed on both sides. A large amount of moisture on the wet film is removed by rolling back and forth with a pressure roller, and 5 ml of 10 ml of cationic dispersed rosin glue aqueous solution (based on the calculated mass of each piece of film) with concentrations of 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, and 4% are evenly coated on both sides of the film by a coating process and allowed to stand for 10 minutes. Then, it is placed in a vacuum flat plate dryer preheated to 95°C and dried for 5 minutes to obtain a cationic dispersed rosin glue-coated corrugated paper-based biodegradable film.

[0133] (5) The mulch films with different application amounts of cationic dispersed rosin glue prepared in the above step (4) were tested for their quantitative properties, thickness, tensile strength, tear strength, burst resistance, folding resistance and water vapor barrier properties according to national standards GB / T451.2-2002, GB / T 451.3-2002, GB / T 455-2002, GB / T 454-2020, GB / T 12914-2018, GB / T457-2018 and GB-T1037-2021. The test results are shown in Table 8.

[0134] Table 8 Physical properties of mulch films applied with different cationic dispersed rosin glues

[0135]

[0136]

[0137] (6) Cut the mulch film with 3% cationic dispersed rosin glue application amount prepared in step (4) above into 17 cm × 17 cm pieces and place them in a constant temperature and humidity chamber with a relative humidity of (50±2)% and a temperature of (23±1)°C for 24 hours. The heat preservation and moisture retention effect is measured in a 5-gallon flower pot filled with 10 kg of red sandy soil with a saturated moisture content of 40% and a weak acidity (pH = 5.7): take out the mulch film after balancing and spread it on the soil surface with a humidity of 40%, and surround it with the corresponding The soil was covered with the same humidity, and then the soil temperature at the 5cm and 10cm tillage layers was measured on the day of mulch film laying, the 7th day, the 14th day, the 21st day, the 28th day, the 35th day, the 42nd day, the 49th day, the 56th day and the 63rd day. After the temperature collection was completed, the soil at the 5cm tillage layer and the 10cm tillage layer was taken respectively, and the soil moisture content was determined by the drying method. In order to compare the effects, a control group (plastic mulch covering and no covering) was made. The heat preservation and moisture retention effect of the glycerol mulch is shown in Figure 2. Fig.23 .

[0138] (7) Determine the biodegradability of the 3% cationic dispersed rosin glue prepared in step (4) above. Surface application degradation: After the temperature measurement in step (6) above is completed, carefully peel off the surface film and use a brush to sweep away the surface soil. Then use softened tap water to repeatedly clean the surface soil, and then place it on a 95°C vacuum flat plate dryer to dry for 5 minutes. Take it out and place it under relative humidity (50±2)% and temperature (23±1)°C for 24 hours to balance it. Then weigh it. The surface application degradation rate is calculated based on the ratio of the mass difference of the film before and after application to the mass of the film before degradation. Soil burial degradation: Cut the film into 16cm×16cm pieces and spread it on a 5cm tillage layer. Attach soil with the same humidity. Take out the film samples 7 days, 14 days, 21 days, 28 days, 35 days, 42 days, 49 days, 56 days and 63 days after the film is buried in the soil to determine its soil burial degradation rate. Fig.24 It is the degradation rate and macroscopic characteristics of mulch film.

[0139] Comparative Example 1: Corrugated paper raw material without degumming and deinking

[0140] (1) The low-recyclable corrugated paperboard / board with ink on the surface is broken into small paper scraps by a paper shredder, 10 g of which is weighed and added into a beaker containing 500 g of softened tap water, and soaked at room temperature for 24 h. The fiber bundles are mechanically stirred at a speed of 2000 rpm for 5 min to dissociate. After the dissociation is completed, the fiber bundles are transferred into a 200-mesh pulp bag and centrifuged in a dehydrating spin dryer to obtain the undegummed and deinked corrugated paper wet pulp.

[0141] (2) Weigh 2.1 g (based on absolute dry fiber) of the wet pulp described in step (1) above into a 250 ml beaker, add 100 g of a 7% sodium hydroxide / 12% urea aqueous solution precooled to -13°C, and mechanically stir at 2000 rpm for 1 min at room temperature to obtain a viscous solution of undegummed and deinked corrugated paper cellulose.

[0142] (3) The heterogeneous mixed viscous solution obtained in the above step (2) was poured into a transparent acrylic mold with an inner diameter of 19.2 cm×19.2 cm, and oscillated on a horizontal rotary oscillator at a speed of 200 rpm for 5 minutes to allow the solution to be cast, defoamed, and flattened. The disordered self-assembled cellulose solution of the undegummed and deinked corrugated paper short fibers evenly penetrated the fiber network structure, and then was placed in a 60°C oven for 6 hours to solidify the ground film by solvent evaporation. After solidification, it was taken out and cooled to room temperature, and then poured into 200 ml of 7% ammonium sulfate solution to further reconstruct the cellulose hydrogen bonds. It was found that the ground film was broken as soon as the hydrogen bond reconstruction liquid was poured in (the breakage rate was basically 100%). This is because: ① The wet pulp raw material is all short fibers, lacking long fibers that play a supporting and stabilizing role; ② The wet pulp raw material also contains a small amount of flocculent colloid, ink, etc., which makes the short fibers, colloids and inks locally enriched during the formation of the ground film network structure, and cannot form a structure with uniform distribution of short fibers and cellulose solution. Therefore, the mechanical properties are extremely poor, and its microstructure is as follows: Figure 1 shown.

[0143] Comparative Example 2: Degummed and deinked corrugated paper raw material

[0144] (1) Corrugated paper boxes / boards with low recycling value and ink on the surface are broken into small paper scraps by a paper shredder, and 20g of corrugated paper is added into a 2L beaker according to the ratio of corrugated paper scraps: sodium hydroxide: water (g:g:ml) 2:3:150, and soaked for 24 hours at room temperature, and then transferred to an ultrasonic instrument with a frequency of 40kHz, and ultrasonicated at 80°C for 1 hour under the condition of 100% ultrasonic power. During the process, the glue and ink foam floating on the surface are manually scraped off by a scraper. After degumming and deinking, the slurry is transferred to a 200-mesh pulp bag and centrifuged by a dehydrating spin dryer to obtain degummed and deinked corrugated paper pulp fiber wet pulp.

[0145] (2) Weigh 2.1 g (based on absolute dry fiber) of the wet pulp described in step (1) above into a 250 ml beaker, add 100 g of a 7% sodium hydroxide / 12% urea aqueous solution that has been precooled to -13°C, and mechanically stir at 2000 rpm for 1 min at room temperature to obtain a viscous solution of degummed and deinked corrugated paper cellulose.

[0146] (3) The heterogeneous mixed viscous solution obtained in the above step (2) was poured into a transparent acrylic mold with an inner diameter of 19.2 cm×19.2 cm, and oscillated on a horizontal rotary oscillator at a speed of 200 rpm for 5 minutes to allow the solution to be cast, defoamed, and flattened. The degummed and deinked corrugated paper short fibers were disorderly self-assembled and the cellulose solution was uniformly distributed between the fiber network structures. The film was then placed in an oven at 60°C for 6 hours to solidify the film by solvent evaporation. After the film was solidified, it was taken out and cooled to room temperature and then poured into 200 ml of 7% ammonium sulfate solution to further reconstruct the cellulose hydrogen bonds. It was found that the solid film was broken as soon as the hydrogen bond reconstruction liquid was poured in (the breakage rate was basically 95%). This is because although the short fibers in the film structure can be evenly assembled, they lack long fibers that play a supporting and stabilizing role, resulting in extremely poor mechanical properties of the film. Its microstructure is as follows: Figure 2 shown.

[0147] Comparative Example 3: Adding cotton linter pulp to degummed and deinked corrugated paper

[0148] (1) Corrugated paper boxes / boards with low recycling value and ink on the surface are broken into small paper scraps by a paper shredder, and 20g of corrugated paper is added into a 2L beaker according to the ratio of corrugated paper scraps: sodium hydroxide: water (g:g:ml) 2:3:150, and soaked for 24 hours at room temperature, and then transferred to an ultrasonic instrument with a frequency of 40kHz, and ultrasonicated at 80°C for 1 hour under the condition of 100% ultrasonic power. During the process, the glue and ink foam floating on the surface are manually scraped off by a scraper. After degumming and deinking, the slurry is transferred to a 200-mesh pulp bag and centrifuged by a dehydrating spin dryer to obtain degummed and deinked corrugated paper pulp fiber wet pulp.

[0149] (2) Weigh 0.3536 g (based on absolute dry fiber) of cotton linter pulp (DP = 9.6 × 104, α-cellulose content > 95%), add it to 100 g of 7% sodium hydroxide / 12% urea aqueous solution that has been precooled to -13°C, and mechanically stir at 2000 rpm for 4 min at room temperature. After stirring, add 1.8564 g (based on absolute dry fiber) of the degummed and deinked corrugated pulp fiber wet slurry described in the above step (2), and continue stirring for 1 min to obtain a viscous mixed slurry with a short fiber network structure built by the degummed and deinked corrugated pulp fibers and a large amount of cellulose solution between the fibers.

[0150] (3) The heterogeneous mixed viscous solution obtained in the above step (2) was poured into a transparent acrylic mold with an inner diameter of 19.2 cm×19.2 cm, and oscillated on a horizontal rotary oscillator at a speed of 200 rpm for 5 minutes to allow the solution to be cast, defoamed, and flattened. The degummed and deinked corrugated paper short fibers were disordered and self-assembled. The cellulose solution uniformly penetrated the fiber network structure, and then placed in an oven at 60°C for 6 hours to solidify the ground film by solvent evaporation. After solidification, the ground film was taken out and cooled to room temperature, and then 200 ml of 7% ammonium sulfate solution was poured into the ground film to further reconstruct the cellulose hydrogen bonds. It was found that the ground film was damaged as soon as the hydrogen bond reconstruction liquid was poured in (the damage rate was basically 100%). Compared with the control example 2, the increase in the amount of low-polymerization degree cellulose solution in the solution caused the viscosity of the system to increase, and the casting distribution resistance of the short fibers in the solution was large, which reduced the interweaving structure of the short fibers. Secondly, the total number of short fibers in the ground film structure was reduced, so the mechanical properties of the ground film were extremely poor. Its microstructure was as follows Figure 3 As shown, Figure 2 The distribution of short fibers and interwoven structures decreases, and the distribution of single fibers increases.

[0151] Comparative Example 4: Adding low amount of long fiber to degummed and deinked corrugated paper, the amount of long fiber is ≤ 6%

[0152] (1) Corrugated paper boxes / boards with low recycling value and ink on the surface are broken into small paper scraps by a paper shredder, and 20g of corrugated paper is added into a 2L beaker according to the ratio of corrugated paper scraps: sodium hydroxide: water (g:g:ml) 2:3:150, and soaked for 24 hours at room temperature, and then transferred to an ultrasonic instrument with a frequency of 80kHz, and ultrasonicated at 80°C for 1 hour under the condition of 80% ultrasonic power. During the process, the glue and ink foam floating on the surface are manually scraped off by a scraper. After degumming and deinking, the slurry is transferred to a 200-mesh pulp bag and centrifuged by a dehydrating spin dryer to obtain degummed and deinked corrugated paper pulp fibers.

[0153] (2) The commercially available long-fiber raw pulp board Simao pine pulp board was broken into small pieces by a paper shredder, 20 g of the shredded pulp board fiber was weighed and added to 1000 g of softened tap water, and the pulp was soaked at room temperature for 6 h, and mechanically stirred at a speed of 2000 rpm for 5 min to dissociate the fiber bundles. After the dissociation was completed, the pulp was transferred to a 200-mesh pulp bag and centrifuged in a dehydrating dryer to obtain the dissociated long-fiber wet pulp.

[0154] (3) Weigh 0.0442 g (based on absolute dry fiber) of the long fiber wet pulp described in step (2) above, add it to 100 g of 7% sodium hydroxide / 12% urea aqueous solution that has been precooled to -13°C, and mechanically stir at 2000 rpm for 4 min at room temperature. After stirring, add 2.1658 g (based on absolute dry fiber) of the degummed and deinked corrugated pulp fiber of step (1), and continue stirring for 1 min to obtain a viscous mixed slurry with low-dosage long and short fibers evenly distributed and the fibers filled with cellulose solution.

[0155] (4) The heterogeneous mixed viscous solution obtained in step (3) was poured into a transparent acrylic mold with an inner diameter of 19.2 cm×19.2 cm, and oscillated on a horizontal rotary oscillator at a speed of 200 rpm for 5 minutes to allow the solution to be cast, defoamed, and flattened. The long and short fibers were disorderly self-assembled and the cellulose solution evenly penetrated the fiber network structure. The film was then placed in an oven at 60°C for 6 hours to solidify the film by solvent evaporation. After the film was solidified, it was taken out and cooled to room temperature and then poured into 200 ml of 7% ammonium sulfate solution to further reconstruct the cellulose hydrogen bonds. After standing for 5 minutes, the film was easily damaged during the pouring of the hydrogen bond reconstruction solution (the damage rate was 90%). The damage rate was basically 100% during the soaking and washing process in softened tap water, indicating that the wet strength of the film formed was extremely low, because the amount of long fibers that played a leading role was too small to bear the tensile force between the entire network structure. Its microstructure was as follows: Figure 4 shown.

[0156] Comparative Example 5: Adding appropriate amount of long fibers to degummed and deinked corrugated paper but the decomposition time is too long

[0157] (1) Corrugated paper boxes / boards with low recycling value and ink on the surface are broken into small paper scraps by a paper shredder, and 20g of corrugated paper is added into a 2L beaker according to the ratio of corrugated paper scraps: sodium hydroxide: water (g:g:ml) 2:3:150, and soaked for 24 hours at room temperature, and then transferred to an ultrasonic instrument with a frequency of 40kHz, and ultrasonicated at 80°C for 1 hour under the condition of 100% ultrasonic power. During the process, the glue and ink foam floating on the surface are manually scraped off by a scraper. After degumming and deinking, the slurry is transferred to a 200-mesh pulp bag and centrifuged by a dehydrating spin dryer to obtain degummed and deinked corrugated paper pulp fibers.

[0158] (2) The commercially available long-fiber raw pulp board Simao pine pulp board was broken into small pieces by a paper shredder, 10 g of the shredded pulp board fiber was weighed and added to 500 g of softened tap water, and soaked at room temperature for 6 h. The fiber bundles were mechanically stirred at a speed of 2000 rpm for 5 min to dissociate the fiber bundles. After the dissociation was completed, the fiber bundles were transferred to a 200-mesh pulp bag and centrifuged using a dehydrating dryer to obtain the dissociated long-fiber wet pulp.

[0159] (3) Weigh 0.3536 g (based on absolute dry fiber) of the long fiber wet pulp described in step (2) above, add it to 100 g of 7% sodium hydroxide / 12% urea aqueous solution that has been precooled to -13°C, and mechanically stir at 2000 rpm for 10 min at room temperature. After stirring, add 1.8564 g (based on absolute dry fiber) of the degummed and deinked corrugated pulp fiber of step (1), and continue stirring for 5 min to obtain a viscous mixed slurry in which the fibers with long fiber dissociation time build a network structure and the fibers are filled with cellulose solution.

[0160] (4) The heterogeneous mixed viscous solution obtained in step (3) was poured into a transparent acrylic mold with an inner diameter of 19.2 cm×19.2 cm, and oscillated on a horizontal rotary oscillator at a speed of 200 rpm for 5 minutes to allow the solution to be cast, defoamed, and flattened. The long and short fibers were disorderly self-assembled and the cellulose solution was uniformly distributed between the fiber network structures. Then, the film was placed in a 60°C oven for 6 hours to solidify the film by solvent evaporation. After the film was solidified, it was taken out and cooled to room temperature and then poured into 200 ml of 7% ammonium sulfate solution to further reconstruct the hydrogen bonds of the cellulose. After standing for 5 minutes, the film was easily damaged during the pouring of the hydrogen bond reconstruction solution (the damage rate was 20%). Pour 100 ml of softened tap water to soak and wash until the sample was neutral. Then, the wet film was spread flat between two filter cloths, and absorbent felt was placed on both sides. A large amount of moisture in the wet film was removed by rolling back and forth with a roller. After being placed in a vacuum flat dryer preheated to 95°C and dried for 5 minutes, 95% of the obtained films had cracks or breaks of varying degrees. This is because during the mixing process of the two fibers, the disintegration time is too long, causing the original long fibers to be broken and shortened to varying degrees, the short fibers to be further broken and shortened, and the ultrafine fiber content increases and is lost during the washing process, resulting in less short fibers that can fill the fiber network structure and the long fiber skeleton structure is insufficient to support the mechanical properties of the film. Figure 5 The figures show different degrees of cracks or fractures and microstructures during the actual film drying process. Compared with the control example 4, the long fibers and short fibers in the microstructure are shorter and the amount of short fibers is reduced, but the relative amount of long fibers is increased.

[0161] The above examples are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there may be many variations, such as replacing corrugated paper with low recycling value with other waste papers with low recycling value, such as waste newsprint, books, magazines, egg trays, etc., and replacing plant long fibers with environmentally non-toxic artificial fibers such as basalt fibers, fly ash fibers, and coal gangue fibers. For those skilled in the art, the present application may have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present application. The selection of terms used in this article is intended to best explain the principles, practical applications, or improvements to the technology in the market of each embodiment, or to enable other ordinary technicians in the field of this technology to understand the embodiments disclosed herein.

Claims

1. A method for preparing a corrugated paper-based biodegradable mulch film, characterized in that: The method comprises the following steps: S1. Soak the corrugated paper scraps in a sodium hydroxide solution with a concentration of 1%-3% at room temperature for 12-24 hours, and then perform ultrasonic treatment; during the ultrasonic process, the rubber and ink foam floating on the surface are manually scraped off with a scraper to obtain the degummed and inked slurry; the degummed and inked slurry is poured into a 200-300 mesh pulp bag for centrifugal separation to obtain degummed and deinked corrugated paper pulp fibers; The solid-to-liquid ratio of the corrugated paper scraps to the sodium hydroxide solution is 1:15 (g:ml); S2. The degummed and deinked corrugated pulp fibers in S1 are crushed to obtain pulp board fibers; the pulp board fibers are added to softened tap water at a solid-liquid ratio of 1:5-1:50 (g:ml), and the fibers are soaked at room temperature for 4-6 hours to perform fiber decomposition, and after decomposition, the fibers are transferred to a 200-300 mesh pulp bag for centrifugal separation to obtain decomposition long fiber wet pulp; S3. Add the long fiber wet pulp of S2 into the alkaline urine solution at a solid-liquid ratio of 1:25-1:2500 (g:ml); then stir for 3-5 minutes at room temperature; after stirring, add the corrugated paper pulp fiber obtained in S1 at a solid-liquid ratio of 1.96%-1.6%; continue stirring for 1-2 minutes to obtain a viscous mixed slurry; The stirring speed is 1000rpm-2000rpm; S4. Pour the viscous mixed slurry obtained in S3 into a mold and shake it, then solidify it. After it is shaped, take it out and cool it to room temperature. Pour 100-300 ml of cellulose hydrogen bond reconstruction liquid into it, let it stand for 3-8 minutes, remove the hydrogen bond reconstruction liquid, and then treat the sample with softened tap water to make it neutral, so as to obtain a wetland film; The curing temperature is 30-60°C and the time is 4-8h; the specific operation of the softened tap water treatment is to repeatedly add 100-300ml of softened tap water, soak for 3-5min and then pour it; S5: Spread the wet film in S4 between two filter cloths, and then place absorbent felt on both sides, remove a large amount of moisture from the wet film by a roller press wet method, and then apply a film performance improvement functional additive to both sides of the film and let it stand for 10-15 minutes, and then place the film in a vacuum flat plate dryer preheated to 60-95° C. and dry it for 10-5 minutes to obtain a corrugated paper-based biodegradable film; The amount of the functional additive for improving the performance of the mulch film is 5-20 ml, and the concentration is 1:5-1:1000.

2. The preparation method according to claim 1, characterized in that: The ultrasonic power of the ultrasonic treatment of S1 is 40%-100%; the temperature is 40-80°C; the time is 5-60min; and the ultrasonic frequency is 40-140kHz.

3. The preparation method according to claim 1, characterized in that: The fiber decomposition is performed at a rotation speed of 500-2000 rpm and for a time of 3-5 minutes.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the long and short fibers in S3 is controlled within the range of 8%-20%.

5. The preparation method according to claim 1, characterized in that: The alkaline urine solution in S3 is a 1%-10% sodium hydroxide / 20%-2% urea aqueous solution that has been precooled to -5 to -20°C.

6. The preparation method according to claim 1, characterized in that: The hydrogen bond reconstruction solution of S4 is one or a mixture of 7% ammonium sulfate solution, 5% sodium sulfate solution, and 5% sulfuric acid solution.

7. The preparation method according to claim 1, characterized in that: The method for removing moisture in S5 is: laying the wetland film flat between two filter cloths, placing absorbent felt on both sides, and removing a large amount of moisture from the wetland film by a roller wet method.

8. The preparation method according to claim 1, characterized in that: The oscillation mode in S4 is up-and-down seesaw oscillation, or horizontal rotary oscillation, or horizontal reciprocating oscillation, or a combination of several oscillation modes, with an oscillation time of 3-10 minutes and a rotation speed of 40-400 rpm.

9. The preparation method according to claim 1, characterized in that: The functional additive for improving the performance of the mulch film of S5 can be one or a mixture of cationic dispersed rosin glue, polyamide epichlorohydrin resin, fly ash, cationic polyacrylamide, cationic starch, carboxymethyl cellulose, alkyl ketene dimer, paraffin emulsion, bis stearamide, phosphate starch, polyethylene oxide, gelatin, polyvinyl alcohol, and glycerol.

10. The preparation method according to claim 1, characterized in that: The method further comprises the following steps: S6: measuring the quantity, thickness, tensile strength, tear strength, bursting strength, folding strength, water vapor barrier properties and composting degradation properties of the corrugated paper-based biodegradable mulch film obtained in S5; S7 measures the heat preservation and moisture conservation effects, surface laying and soil burial degradation degree, and crop planting effects of the corrugated paper-based biodegradable mulch obtained in S5.

Citation Information

Patent Citations

  • Full-degradable cyanobacteria-based bioplastic and preparation method thereof

    CN107057247A

  • Method for preparing environment-friendly bast fiber mulching film by using lapping-papermaking combined method

    CN107996233A

  • Method for repairing secondary fiber or recycled fiber keratinization

    CN108755212A

  • Secondary fiber-based insect-proof full-degradable mulching film for cigarettes and manufacturing method of secondary fiber-based insect-proof full-degradable mulching film

    CN111749041A

  • Preparation process of environment-friendly waterproof corrugated carton

    CN114108386A